LEGAL PROBLEMS OF USING HUMAN GENETIC INFORMATION IN THE RUSSIAN FEDERATION - KAZAKOV Nikita Andreevich; AKHTYAMOVA Evgeniya Viktorovna (Правовое государство: теория и практика, 2022)
The article analyzes the issues arising when using human genetic information. The study of the existing legislation governing the use of such information reveals problems in determining the legal nature of genetic information in the personal data system, as well as its adequate legal protection. Purpose: to identify the legal problems of the use of genetic information on the basis of international legislation, judicial practice and the current Russian legislation and to identify possible ways of their solution. Methods: comparison, description and interpretation, dialectical, for-mal-logical, structural-system analysis and synthesis. Results: the study allows to de-termine the current state of legal regulation of genetic information, as well as to out-line ways of solving legal problems in this area.